NEW DISTRIBUTION OF SPOTTED GARDEN EEL Heteroconger guttatus ALLEN, ERDMANN & MONGDONG, 2020 (ANGUILLIFORMES, CONGRIDAE, HETEROCONGRINAE) FROM SAPARUA ISLAND, THE MOLUCCAS, INDONESIA - Nadia Mahriza; Gino Limmon; Ahmad Kadafi; Abigail Moore; Kunto Wibowo (BRIN Publishing (Penerbit BRIN), 2025)
Two specimens of garden eel (384.3–398.0 mm total length) were collected from Saparua Island,the Moluccas, Indonesia, and identified as Heteroconger guttatus Allen, Erdmann & Mongdong, 2020.These specimens represent the westernmost record of this species, which was previously only knownfrom its type locality in Venu Island, West Papua Province, Indonesia.